2021
DOI: 10.1186/s12935-021-02409-6
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis identifies IFI16 as a novel signature associated with overall survival and immune infiltration of skin cutaneous melanoma

Abstract: Background Skin cutaneous melanoma (SKCM) is the most common skin tumor with high mortality. The unfavorable outcome of SKCM urges the discovery of prognostic biomarkers for accurate therapy. The present study aimed to explore novel prognosis-related signatures of SKCM and determine the significance of immune cell infiltration in this pathology. Methods Four gene expression profiles (GSE130244, GSE3189, GSE7553 and GSE46517) of SKCM and normal skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…In our systems model, one group demonstrated that IFI16, normally restricted to the nucleus, could be induced to appear in the cytoplasm under conditions of UV radiation-induced cell injury [ 78 ]. Furthermore, IFI16 has been shown to be a novel signature associated with overall survival and immune infiltration of skin cutaneous melanoma [ 79 ].…”
Section: Various Biomarkers Tied To Uva Exposure and To Melanomamentioning
confidence: 99%
“…In our systems model, one group demonstrated that IFI16, normally restricted to the nucleus, could be induced to appear in the cytoplasm under conditions of UV radiation-induced cell injury [ 78 ]. Furthermore, IFI16 has been shown to be a novel signature associated with overall survival and immune infiltration of skin cutaneous melanoma [ 79 ].…”
Section: Various Biomarkers Tied To Uva Exposure and To Melanomamentioning
confidence: 99%